Faktor - faktor Penyebab Kelelahan Mata pada Pekerja di Optik Kornea - Wahyu Pamungkas; Wahyu Budiana; Zakaria Efendi (Akademi Refraksi Optisi dan Optometry Gapopin, 2023)
This study aims to determine the factors that cause eye fatique in workers at Kornea optics during their work activities. The method used in this research is descriptive qualitative by observing and studying documents. The result showed that the variables of age, consumption of drugs, diabetes mellitus, hypertension and the level of room lighting are factors affecting workers’ eye fatique